(untitled) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the problems of national-socialistic mythological creative work. The main functions of political myth, propagation of "Fuhrer-myth" by Nazi propaganda and the role of Ministery of Propaganda of the Third Reich Joseph Goebbels in this process are covered in the article.